Behaviosec partners with Nationwide and Unisys on behavioural biometrics app. (May 2016) - Unknown
Abstract : Behaviosec has partnered with UK bank Nationwide and Unisys to build a prototype app based on behavioural biometrics. Behaviosec says the prototype is still in its early stages